Компьютерные технологии и графика: атлас; учебное пособие - Учаев П. Н. Петр Николаевич; Емельянов С. Г. Сергей Геннадьевич; Учаева К. П. Капиталина Павловна; Попов Ю. А. Юрий Алексеевич (Старый Оскол, ТНТ, 2019)
Авт. указаны на обл.